2007
DOI: 10.1002/ca.20494
|View full text |Cite
|
Sign up to set email alerts
|

The basilar venous plexus

Abstract: The basilar venous plexus is the anteromedian venous channel of the posterior cranial fossa that has many conflicting and brief descriptions in the extant literature. To our knowledge, no single study has been performed that analyzed this venous structure in detail. The aim of the current study was to elucidate further the anatomy of this structure of the posterior cranial fossa. The authors examined twenty adult cadaveric specimens following injection of the internal jugular veins or cavernous sinus to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A few into the jugular bulb via the PVC and the inferior petrosal sinus [5,22]. These communicating sinuses may show individual variations in size, a feature that explains why we found varying diameters for the PVC [9,23]. In addition, as these interconnecting dural spaces are filled by the venous blood homogeneously, their dimensions are relatively uniform without major changes at different levels.…”
Section: Resultsmentioning
confidence: 75%
“…A few into the jugular bulb via the PVC and the inferior petrosal sinus [5,22]. These communicating sinuses may show individual variations in size, a feature that explains why we found varying diameters for the PVC [9,23]. In addition, as these interconnecting dural spaces are filled by the venous blood homogeneously, their dimensions are relatively uniform without major changes at different levels.…”
Section: Resultsmentioning
confidence: 75%
“…19 Tubb et al have also written 2 excellent articles on the tectorial membrane and the basilar venous plexus. 20,21 REDH could be associated with retroclival subdural hematomas (RSDHs), particularly in violent injuries, as in our second patient. 6 Isolated RSDHs are rarer than REDHs: only 7 cases have been reported, [22][23][24][25][26][27][28] but the context, clinical presentation, and mechanisms of formation are different.…”
Section: Michaelmentioning
confidence: 62%
“…20 Noting similarities between blast and ballistic waves, a recent paper estimated mild traumatic brain injury (TBI) thresholds for the thoracic mechanism of blastinduced TBI by analyzing data from ballistic pressure wave and behind armor blunt trauma studies. 21 A myth is an assertion that has either been disproved by careful experiment or for which there is no historical or scientific evidence in cases where it is reasonably expected. Belief in the remote effects of penetrating projectiles may have originated with hunters and soldiers, but their reality is now well established in a broad body of scientific literature, even though the clinical significance for the practicing neurosurgeon might be debatable.…”
Section: Julian Prellmentioning
confidence: 99%
“…in this particular type of shunt, the lesion involves mainly the epidural space and is in direct contact with the adjacent osseous structures that may invade or recruit the blood supply from the spongy bone structures and has no primary role in the drainage of the central nervous system. Tubbs et al reported that a communication was always found between the basilar venous plexus and the inferior petrosal sinuses in a cadaver study 19 . A cadaver study reported by kunicki et al showed 96% (47/50) of the basilar venous plexus drained into the inferior petrosal sinus 20 .…”
Section: Discussionmentioning
confidence: 95%